2013
DOI: 10.1097/qai.0b013e31828f93bb
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Mycobacterium tuberculosis Infection in HIV-Positive Patients Is Associated With CARD8 Genetic Variant

Abstract: HLA and other genetic variants, playing an important role in innate and adaptive immunity, are known to influence tuberculosis (TB) development in HIV-1-positive (HIV+) patients. Because inflammasome genes contribute to HIV-1 susceptibility, we investigated the possible association between polymorphisms in inflammasome genes with HIV-1 and Mycobacterium tuberculosis coinfection (HIV+TB+) in a case/control cohort of Brazilian individuals. Nineteen single-nucleotide polymoprhims in 8 inflammasome genes (NLRP1, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
1
30
1
2
Order By: Relevance
“…Renewed global interest led to advances in recognising TB/HIV co-infection and understanding the mechanisms promoting susceptibility of HIV-infected people in developing TB disease as part of a multifactorial process [26-30]. Diagnosis of HIV/TB co-infection in children is still challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed global interest led to advances in recognising TB/HIV co-infection and understanding the mechanisms promoting susceptibility of HIV-infected people in developing TB disease as part of a multifactorial process [26-30]. Diagnosis of HIV/TB co-infection in children is still challenging.…”
Section: Resultsmentioning
confidence: 99%
“…A recent case-control study in Brazil showed the novel association between certain inflammasome gene polymorphisms (i.e. CARD8 genetic variants) and the development of TB infection in HIV positive subjects [30]. …”
Section: Impact Of Hiv On Pathogenesis Of Tbmentioning
confidence: 99%
“…DNA (Hirako et al, 2015) or phospholipid-specific Abs can activate the inflammasome in monocytes (Muller-Calleja et al, 2015; Prinz et al, 2011). Moreover, in some TB studies, inflammasome activation has been linked to bacterial control (Carlsson et al, 2010; Eklund et al, 2014; Mishra et al, 2010; Pontillo et al, 2013). Thus, our data suggest that Abs could direct inflammasome activation in macrophages, and this may contribute to bacterial control.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using a genomewide screening approach in M. tuberculosis-infected vs. noninfected dendritic cells, Barreiro et al (2012) found a number of expression quantitative trait loci that associate with tuberculosis in this system, and imputation of 1000 Genomes Project data (1000Genomes Project Consortium et al, 2012 into a Ghanaian genomewide data set (tuberculosis cases and healthy controls) revealed a resistance locus at 11p13 downstream of WT1 (Thye et al, 2012). Recently, susceptibility to tuberculosis in HIV-1-infected individuals was associated with a CARD8 genetic variant (Pontillo et al, 2013), and a genotype resulting in high IL-10 production also appeared to predispose HIV-1-infected individuals to TB infection (Ramaseri Sunder et al, 2012). Recently, susceptibility to tuberculosis in HIV-1-infected individuals was associated with a CARD8 genetic variant (Pontillo et al, 2013), and a genotype resulting in high IL-10 production also appeared to predispose HIV-1-infected individuals to TB infection (Ramaseri Sunder et al, 2012).…”
Section: The Role Of Host Genetic Variationmentioning
confidence: 99%